Association of 2D:4D digit ratio with frailty and MMSE - Gonçalves, Celina (2019)
The 2D:4D ratio is an indicator of prenatal testosterone exposure (Fink, Manning, & Neave, 2006) and it is a fairly stable one (Anders, 2007). While there are some studies about the role of testosterone on frailty (Srinivas-Shankar & Wu, 2009) and cognitive decline (Moffat, 2005) in older adults, very few analyze the impact of prenatal testosterone exposure (Halil et al., 2013). Our aim was to understand the relation between 2D:4D ratio, frailty and cognitive decline in community-dwelling elderly people.